How can a software innovate Latin teaching - Cortinovis, Luca; Stabile, Francesco (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
The history of books demonstrates how the evolution of formats has changed both the organization of content and its consumption. The challenge posed by the digital revolution requires a profound reconsideration of the educational offerings to support teachers in their essential profession. The widespread use of digital devices has created a demand for effective digital tools applied to education, which has not yet received an adequate response.